Enhancement effect of urea toward electroporation-mediated plasmid transfection efficiency in the HEK-293 cell line - Mahshid Mowla; Gilar Gorji-Bahri; Hamid Reza Moghimi; Atieh Hashemi (Research in Pharmaceutical Sciences)
Intracellular delivery is crucial in biological and medical studies. Although many molecular tools have been created for cell-based gene therapies, it remains challenging to introduce external molecules into cells. As one of the most popular non-viral transfection methods, electroporation induces transient pores in the cell membrane by applying an external electric field. Unsatisfactory transfection efficiency and low cell viability are the major drawbacks of electroporation. To overcome these issues, the current study investigated the effect of urea on electroporation-mediated transfection efficiency. Experimental approach: Three voltages of electroporation, including 100, 120, and 140 V, and 3 concentrations of urea buffer, including 0.25%, 0.5%, and 1% W/V, were considered as variables in this study. The HEK-293 cell line was used for transfection, and green fluorescent protein (GFP) expression was evaluated using flow cytometry and fluorescence microscopy. Findings/Results: The results showed that the combination of electroporation and urea increased electroporation efficacy, but the effect depended on voltage and urea concentration. When different concentrations of urea were added to HEK-293 cells at a voltage of 100 V, the number of cells transfected by pEGFP-N1 increased (from 12.3 ± 0.2% in untreated cells to 17.35 ± 0.55%, 23.3 ± 0.3%, and 14 ± 0.1% at urea concentrations of 0.25%, 0.5%, and 1% W/V, respectively). The electroporation buffer containing 0.5% W/V urea showed the highest EGFP expression (23.3 ± 0.3%) and high cell viability (over 90%). Conclusion and implications: This research offers a new perspective for improving gene transfection efficiency once electroporation is utilized.